Relationship between Family Support, Self-Efficacy and Relapse Occurrence among Youth Recovering from Drug Addiction in Selected Rehabilitation Centres in Limuru Sub-County, Kenya - Wangithi , I. Kinyua; Ndurumo , Michael M. (African Journal of Education,Science and Technology (AJEST), 2020)
A lot of research has been done to understand substance addiction; a life lasting relapsing illness in which uncontrollable drug taking persists despite of serious negative consequences" (Ilze, 2014). The purpose of the study was to identify if there is a relationship between support from the family, self-efficacy and relapse or recidivism behavior to drug use among youth recovering from addiction at the selected rehabilitation centres of Limuru sub-county in Kenya. The study was guided by the social learning theoretical framework. The study used the co-relational research design using 80 youth recovering from drug addiction who were selected using the convenience sampling method. Snowballing sampling method was used to select the 5 centres where the respondents were sleeved from. Data was collected using questionnaires. The level of support provided by family members was measured using the Family Support and Strain tool developed by Schuster, Kessler and Asseltine (1990). The respondents’ self-efficacy was measured using the Drug Avoidance Self-Efficacy Scale (DASES) (Martin, 1992). Data was analyzed in accordance with the stated hypothesis that guided the study; Three-way Chi-square test and Pearson Correlation of Coefficient were used for the inferential statistics. For descriptive analysis, frequency distribution, central tendency and dispersion were used. Logical regression was used to establish the cause effect relationships between the three variables. The results of the analysis showed that majority of the respondents (27%) were aged between 30-35 years, 23% were aged between 22-25 years, 22% between 26-29 years, 16% between 36-39 years, while 13% of them were aged between 18-21 years. Majority of the respondents (65%) were male, while (35%) of them were female. The findings also showed that majority of youth in the rehabilitation centers are well educated (36%) with college and undergraduate certifications and a majority of the respondents (42%) were unemployed. Additionally, 76.6% of the respondents had a high self-efficacy, while (23.4%) of the respondents had a low self-efficacy. The results also showed that family support has a significant relationship with self-efficacy (χ = 19.446; p = 0.026 < 0.05). Because it significantly affects the level of self-efficacy among youth recovering from drug addiction, family support was found to have a significant negative Pearson correlation to relapse (r = -0.628; p = 0.032 < 0.05), implying that family support and relapse had a strong correlation. The Chi-square test on family support and relapse showed that family support and relapse had a significant chi-square value. Further analysis indicated that a unit increase in family support would lead to a 40.7% increase in self-efficacy. Additionally, a unit increment in family support would cause a 38% decrease in chances of relapse. The results implied that the age and employment status influence the level of self-efficacy while gender and education level do not have significant impacts on self-efficacy but education and employment status have a significant relationship with relapse. From these findings, it was concluded that increased family support lead to an increment in self-efficacy and a reduction of the chances of relapse. Additionally, positive change in age and employment status positively affects self-efficacy while an increment in education level and accomplishments in employment would significantly minimize chances of relapse. It is therefore recommended that addiction counselors should consider facilitating family support for their clients in recovery after discharge as an approach of avoiding relapse, that individuals recuperating from substance addiction should be assisted to understand the role their family’s interaction and dynamics plays in their recovery process and NACADA and the Ministry of Health should design policies based on the study’s findings that will benefit addiction treatment practitioners in relapse prevention.